Perkembangan Penelitian Corporate Social Responsibility (CSR) Di Indonesia Selama 15 Tahun (Perspektif Studi Literatur) - Gressy, Gressy; Setiawan, Temy (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
Abstrak The purpose of this research is to (1) explain the commonly factors are researched in academics and are thought to be variables that influence Corporate Social Responsibility; (2) explain the phenomena that drive research in the realm of Corporate Social Responsibility; (3) explain the theories are generally used in corporate social responsibility research. This research is a qualitative descriptive research with a literature observation approach. The data used in this research is a research articles on Corporate Social Responsibility from the peroid the 2008-2023 indexed by Sinta 1-3. The research findings reveal that there are a total of 117 factors suspected to influence Corporate Social Responsibility, and numerous issues/phenomena underlie Corporate Social Responsibility research during the 2008-2023 period. One prevalent issue motivating Corporate Social Responsibility research is the enactment of Law No. 40 of 2007 concerning Limited Liability Companies. PT. Additionally, 39 theories commonly serve as references for Corporate Social Responsibility-related research.